Industrial Internet education: Issues and opportunities - Pimentel, Juan R. (2014)
We propose an approach for addressing the challenges and meeting the needs of industrial networking education. The approach is based on using open source resources, key networking technologies, and an experimental framework to revolutionize the way industrial networking ought to be taught at higher learning institutions around the world. Based on the approach a new type of industrial networking course has been designed, developed, and offered with positive outcomes.